Ultrasensitive, Biocompatible, Self-Calibrating, Multiparametric Temperature Sensors - Zhao, Haiguang; Vomiero, Alberto; Rosei, Federico (Small (Weinheim an der Bergstrasse, Germany), 2015)
Core–shell quantum dots serve as self‐calibrating, ultrasensitive, multiparametric, near‐infrared, and biocompatible temperature sensors. They allow temperature measurement with nanometer accuracy in the range 150–373 K, the broadest ever recorded for a nanothermometer, with sensitivities among the highest ever reported, which makes them essentially unique in the panorama of biocompatible nanothermometers with potential for in vivo biological thermal imaging and/or thermoablative therapy.